2019
DOI: 10.1021/acscatal.9b02523
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Ring-Opening of Donor–Acceptor Cyclopropanes with Primary Arylamines Catalyzed by a Chiral Heterobimetallic Catalyst

Abstract: An efficient catalytic asymmetric ring-opening reaction of donor–acceptor cyclopropanes with primary arylamines was developed. The reaction was achieved through the utilization of a chiral heterobimetallic catalyst, delivering a variety of chiral γ-amino acid derivatives in up to 93% yield and 99% ee. Stereochemical experiments suggest a dominant role for kinetic resolution in this asymmetric process, which is supported by a computational study of the reaction coordinate. A class of chiral bimetallic Lewis aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…It consisted of metals coordinated with chiral phosphoric ligands, offering new perspectives in asymmetric catalysis. 80 In general, metal ions are often used as a Lewis acid agent. The addition of an organic chiral ligand reduces the acidity of the metal Lewis acid significantly.…”
Section: Reaction Selectivity Studies Using Hybrid Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It consisted of metals coordinated with chiral phosphoric ligands, offering new perspectives in asymmetric catalysis. 80 In general, metal ions are often used as a Lewis acid agent. The addition of an organic chiral ligand reduces the acidity of the metal Lewis acid significantly.…”
Section: Reaction Selectivity Studies Using Hybrid Methodsmentioning
confidence: 99%
“…The authors found that the Y(III)/Yb(III) bimetallic catalyst produced high yield and selectivity under controlled conditions. 80 To understand the selectivity and reactivity of this catalyst, the two-layer ONIOM (B3LYP/(6-31G(d) (for non-metals), SDD (for metals)):UFF) was exploited for geometry optimization and single point calculations with m-xylene as implicit solvent using the SMD model. The initial geometry is based on the X-ray crystallographic data.…”
Section: Reaction Selectivity Studies Using Hybrid Methodsmentioning
confidence: 99%
“…Recently, Wang and coworkers described a ring-opening reaction with primary arylamines using a chiral heterobimetallic catalyst (Scheme 19). 63 Enantioenriched γ-amino acid derivatives such as 87− 90 were produced in good yields by combining Y(OTf) 3 and the metal binaphthyl phosphate catalyst (R)-Yb[P] 3 (86). Only traces of the ring-opened products were obtained in the presence of Y(OTf) 3 or (R)-Yb[P] 3 alone, showing the unique activity of this bimetallic system.…”
Section: Ring-opening Reactionsmentioning
confidence: 99%
“…The combination of Y(OTf) 3 with ( R )‐Yb[ P ] 3 greatly enhanced the activity and enantioselectivity more than that with each individual metal salt. Experimental and DFT calculation studies suggested that this reaction proceeded via a two‐step S N 2/proton transfer mechanism, in which the S N 2 process is the rate‐ and enantiodetermining step [11] …”
Section: Asymmetric Reactions Of 2‐substituted Cyclopropane‐11‐dicarboxylatesmentioning
confidence: 99%
“…Experimental and DFT calculation studies suggested that this reaction proceeded via at wo-step S N 2/proton transfer mechanism, in which the S N 2p rocess is the rate-and enantiodetermining step. [11] Asymmetric ring-opening of cyclopropanes using oxygencontaining nucleophiles provided enantioenriched g-hydroxybutyric acid derivatives.T he challenge of the water nucleophile was the competitive further reaction of the opened alcohol product. Tang et al successfully employed chiral Cu II / L2 to promote water-initiated nucleophilic opening, in which Cu(ClO 4 ) 2 •6 H 2 Oa cted as both aL ewis acid and ab uffer of the water source,t hus providing an elegant solution to the controllable release of water as an ucleophile.ADY KAT dominated this reaction leading to electron-rich aryl-substituted racemic cyclopropanes (Scheme 5a).…”
Section: Asymmetric Ring-openings With Nucleophilesmentioning
confidence: 99%